Thysanopteren aus der Türkei (Thysanoptera). - Blunck, Hans (Contributions to Entomology = Beiträge zur Entomologie, 1958)
There is given a list of Thysanoptera, collected by the author in Turkey 1949 with complementary notes on the food plants and localities.